Direct observation of fast protein folding: the initial collapse of apomyoglobin. - Ballew, R M (1996)
The rapid refolding dynamics of apomyoglobin are followed by a new temperature-jump fluorescence technique on a 15-ns to 0.5-ms time scale in vitro. The apparatus measures the protein-folding history in a single sweep in standard aqueous buffers. The earliest steps during folding to a compact state are observed and are complete in under 20 micros. Experiments on mutants and consideration of steady-state CD and fluorescence spectra indicate that the observed microsecond phase monitors assembly of an A x (H x G) helix subunit. Measurements at different viscosities indicate diffusive behavior even at low viscosities, in agreement with motions of a solvent-exposed protein during the initial collapse.